Modification of Recycled HDPE Composite with OPEFB Microfibers Through the Melt Blend Extruder Process - Zulnazri Zulnazri; Rozanna Dewi; Agam Muarif; Ahmad Fikri (International Forum of Researchers and Lecturers, 2024)
This study describes the manufacture of modified composites from recycled HDPE plastic waste and TKKS fibers. The comparison of matrix composition with TKKS fibers used is (70:30); (80:20) and (90:10) %. The mixing process of HDPE with OPEFB was carried out using the melt blending method and extruded to obtain composite pellets. Composite characterization obtained high tensile strength in HDPE composites: OPEFB ratio (70:30) % of 36.50 Mpa, while the tensile strength of HDPE: OPEFB ratio (80:20) and HDPE: OPEFB ratio (90:10) % were obtained respectively 23.50 MPa and 26.50 MPa. The results of the surface structure test with SEM showed that there was a bond between the HDPE matrix and TKKS fibers which was marked by a brittle fracture shape on the surface of the composite and the fibers were not uniformly broken. The impact test results of HDPE composite: OPEFB ratio (80:20) % have a high impact value of 0.363168 Joules. The FT-IR test results show deformation of C-H vibrations and pyranose C-O-C which are typical of OPEFB at wave numbers 1070.49 & 1151.50 cm- and intermolecular O-H bending in TKKS at wave numbers 3672.47 cm-. The TGA test results of HDPE composite: OPEFB ratio (70:30) and HDPE: TKKS (80:20) obtained degradation temperature values (Te) of 535.57ᴼC and 529.74ᴼC, respectively.